OVER TÜMÖRÜNÜ ANDIRAN BİR TÜBERKÜLOZ HİDROSALPİNKS OLGUSU - CERRAH CELAYİR, Ayşenur and YALTI, Serap and ASİL, Zeynep and İNALHAN, Meral and DAYICIOĞLU, Vedat (Cerrahpaşa Medical Journal, 2014)
Background and Observation.-Tuberculosis of female genital organs in adolescent has been rarely reported. In the most common form, involvement of the fallopian tubes and coexistence of endometritis is seen. On occasion, tuberculous salpingitis can be easily misdiagnosed as adnexial tumour or acute appendicitis. An 11 yearold girl was referred to our clinic from another hospital for the right ovarian tumour and ascites. She was evaluated with clinical and laboratory exams, PPD, ultrasound and computed tomography as well as the cytologic examination of the peritoneal fluid. Tuberculosis was diagnosed and antituberculous chemotherapy with izoniazid, rifampin and pyrazinamide was initiated. The response to chemotherapy was excellent, clinical findings disappeared in one month and all radiological findings disappeared in three months. Tuberculosis still represents a severe problem in many developing countries of the world. For this reason on should think about tuberculosis in adolescent girls with pelvic and abdominal pathology.